Teaching ethics beyond the Academy: Educational tourism, lifelong learning and phronesis - Pitman, Tim; Broomhall, S.; Majocha, E. (National Institute of Adult Continuing Education (NIACE), 2011)
Universities traditionally construct ethical, as well as educational goals in their mission, which they attempt to promote not only through their graduates, but sometimes directly to the wider community. This study explores how targeting lifelong learners through the medium of educational tourism might be one such way in which universities can impart moral and ethical lessons, through a pedagogical construction based on the Aristotelian notion of practical wisdom (phronesis). A qualitative analysis of surveys and interviews conducted with educational tourism providers, lifelong learners, and academic scholars, reveals that whilst intentional learning is central to educational tourism and much of that learning is values-based, the ability of a university to engage with a wide cross-section of people through this medium is not without its problems.